REMOVAL IMPURITIS GARAM DENGAN METODE PERTUKARAN ION SECARA BATCH - Pujiastuti, Caecilia; Yustina Ngatila (2477 - 6165, 2019)
Salt is one of the consumer and industrial consumption products that has the maincontent of sodium chloride (NaCl). The present quality of the salt product currentlycontains about 90-93% sodium chloride, and the other is known as an impurities ofcalcium (Ca), magnesium (Mg), potassium (K) and sulfate (SO4) ions. The presence ofthese impurities will decrease the quality of the salt product, so a method is needed todecrease the content of impurities in the salt product. One of the methods that can beused to reduce the levels of impurities such as Ca, Mg, K, and sulfate (SO4) ions in saltsolution is ion exchange method. In this study we studied the effect of cation resinamount (50-150) grams per liter of salt solution and anion solution (150 grams) andcontact time (5-25) minutes on removal of Ca, Mg, K and SO4 ions. The study wasconducted in a stirred tank with a fixed rotation speed of 200 rpm, and the initial qualityof the salt solution contained Ca ions: 0.07%, Mg: 0.09%, K: 0.04% and SO4: 0.4%.Based on the result of the research, the removal of Ca ion: 93.6%, Mg: 78.93%, K:25.00% dan SO4: 85.47 % at condition of cation resin amount: 150 gram/liter andcontact time 25 minutes.